Cement pastes with UV-irradiated polypropylene: Fracture energy and the benefit of adding metakaolin. (20th March 2018) - Coopamootoo, Kumaran; Masoero, Enrico
Highlights: Micro-sized polypropylene powder is added to portland cement pastes. UV pre-irradiation of the polypropylene leads to composites with improved strength. Polypropylene addition and UV treatment, each increase fracture energy up 10 times. Adding metakaolin to the mix further amplifies the mechanical performance. Abstract: Adding fine plastic-based aggregates to cement pastes can allow for recycling waste while increasing the tensile strength and fracture toughness of the paste. However, the hydrophobicity of plastic causes poor cohesion with the cement paste, affecting the mechanical properties of the composite. Pre-irradiation with UV-C light reduces the hydrophobicity of the plastic, thus increasing the tensile strength of the paste while preserving compressive strength. This paper presents new experimental results, mainly showing that: (i) UV-C irradiated micro-sized polypropylene powder increases the tensile strength and fracture energy of CEM-I cement pastes; (ii) blending cement with metakaolin amplifies the positive effect of polypropylene addition in both untreated and UV-treated forms. These findings indicate that cement-metakaolin pastes containing UV-irradiated polypropylene may be an asset when crack resistance is key, such as in nuclear waste storage and oil/gas well cementing.